2021
DOI: 10.7150/ijbs.54401
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type IDH1 inhibits the tumor growth through degrading HIF-α in renal cell carcinoma

Abstract: The purpose of our study was to explore the effect and intrinsic mechanism of wild-type IDH1 and its substrate α-KG on renal cell carcinoma (RCC). IDH1 was observed lower expression in RCC cell lines. Phenotype experiment was carried out in the wild-type IDH1 and mutant IDH1 R132H plasmid treated cell line. The results showed that the wild-type IDH1 could significantly inhibit the proliferation, migration and promote the apoptosis of RCC cell lines, which were consistent with the IDH1's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…At present, there is little evidence related to AKG alterations in kidney diseases, such as increased urinary excretion in diabetic nephropathy in humans [ 44 ] and mice [ 78 ]; however other report decreased urinary levels in humans and mice [ 42 , 79 ] and reduction of blood serum AKG concentration in diabetic nephropathy in mice [ 41 ]. On the other hand, in RCC, contrary results were found in tissue with an elevated concentration in mice [ 80 ] compared to low levels reported in human samples [ 81 ].…”
Section: Alpha-ketoglutaratementioning
confidence: 98%
See 1 more Smart Citation
“…At present, there is little evidence related to AKG alterations in kidney diseases, such as increased urinary excretion in diabetic nephropathy in humans [ 44 ] and mice [ 78 ]; however other report decreased urinary levels in humans and mice [ 42 , 79 ] and reduction of blood serum AKG concentration in diabetic nephropathy in mice [ 41 ]. On the other hand, in RCC, contrary results were found in tissue with an elevated concentration in mice [ 80 ] compared to low levels reported in human samples [ 81 ].…”
Section: Alpha-ketoglutaratementioning
confidence: 98%
“…In CKD patients, decreased urinary levels of AKG have been reported [ 42 ], whereas there are no differences in AKI patients [ 176 ]. In RCC, AKG urinary excretion is increased [ 177 ], whereas, in biopsies, reduced levels have been reported; even more, tissue levels of this metabolite could be helpful in the prognosis of this neoplasia [ 81 ].…”
Section: Clinical Significance Of Tca Metabolitesmentioning
confidence: 99%
“…Mutations in IDH1 reduce IDH1’s catalytic activity and activate HIF-1 α in glioblastoma cells ( 55 ). Wild-type IDH1 suppresses tumor development in renal cell carcinoma via degrading HIF-α ( 56 ). By using GSEA to examine the variations in cellular activities and pathways between high and low risk groups, we found that metabolic processes and pathways associated with hypoxic state were upregulated, but immune response processes were generally downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, α-ketoglutaric acid accumulation and TCA cycle obstruction 14 . On the contrary, IDH1 gene mutation results in a new activity of the isocitrate dehydrogenase (IDH) enzyme, which catalyzes the reduction of α-KG to 2HG and thus reduces the accumulation of α-KG 15 . In addition, L2HG is involved in angiogenic mimicry (VM) formation in ccRCC cell lines by decreasing PHLDB2 expression or promoting activation of erK1/2 pathway 16 .…”
Section: Metabolic Reprogramming In Tumor Cellsmentioning
confidence: 99%